Peningkatan Keterlibatan Aktif Siswa melalui Penerapan Papan Transformasi Geometri (PATAGI) di Pamboang - Nurmia Nurmia; Nabila Apriani Maulidiah Putri; Mukarrama Mukarrama; Hestiani Hestiani; Andika Andika; Andi Heriani; Abdilla Nurul Azisah; Lukman Lukman (Pakis Journal Institute, 2026)
This community service activity was conducted at SMPN 1 Pamboang to introduce PATAGI (Geometry Transformation Board) as an interactive learning medium for geometry transformation material. The main problem identified was that students still experienced difficulties in understanding the concepts of translation, reflection, rotation, and dilation because the material was considered abstract, and learning activities were generally carried out in a conventional manner. The implementation methods included preparation, implementation, and evaluation stages through socialization, demonstrations, direct practice, group discussions, interactive quizzes, and questionnaire distribution. The results showed that the use of PATAGI helped students understand geometry transformation concepts in a more concrete and visual manner. Students became more active, enthusiastic, and confident in solving problems directly using the provided learning media. In addition, PATAGI created a more interactive and engaging learning atmosphere. Based on the evaluation and questionnaire results, both students and teachers gave positive responses to the use of PATAGI in mathematics learning.